PENGARUH PENERAPAN PENDEKATAN PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MATEMATIKA LANJUT SMA NEGERI 8 MANDAU - Prawito, Yorico (Jurnal Edukasi dan Penelitian Matematika, 2025)
Learners are capable of being problem solvers, and mathematics is no exception. However, in class XI Advanced Mathematics at SMAN 8 Mandau still lacks the necessary skills in this area. The lack of thorough and accurate problem solving in accordance with the set indicators is shown by the research results. To overcome this problem, the RME learning approach was applied. A quantitative approach using a quasi-experimental design was used in this study. With a P-value = 0.039, the null hypothesis (H0) was rejected in the final test analysis using t-test at 0.05 level of significance. In particular, when compared to those who used the conventional learning approach, the Advanced Mathematics XI class at SMAN 8 Mandau outperformed in terms of problem solving with the RME method.Keywords – Realistic Mathematics Education (RME) Learning Approach, Conventional Learning, Mathematical Problem Solving